Permasalahan Implementasi Kurikulum Merdeka di Kelas V B SDN 34/1 Teratai - Marwiyah, Siti; Syafitri, Syarifah; Isratulhasanah, Puji; Darmawan, Hanif; Fransiska, Afiona; Nurrahmah, Silva; Khoirunnisa, Khoirunnisa (LPPM Institut Pendidikan Nusantara Global, 2024)
The Merdeka Curriculum is a curriculum launched by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) in 2022 as an effort to address the challenges and crises in education caused by the COVID-19 pandemic. This study aims to investigate the implementation of the Merdeka Curriculum at SDN 34/1 Teratai, particularly in class 5B. The methodology used is a qualitative approach using descriptive methods with data collection methods through observation, interviews, and document analysis. The findings of this research are: 1) Implementation of the Merdeka Curriculum, 2) Challenges related to the implementation of the Merdeka Curriculum, 3) Solutions to overcome challenges in implementing the Merdeka Curriculum in class VB of SDN 34/1 Teratai.